HUBUNGAN MOTIVASI DENGAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Yuliani, Desi; Nasrul, Nasrul; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This study aims to determine relationship between motivation with students learning outcomes in learning social studies in the fourth grade. This type of research is correlational research. The population of this research is the fourth grade students of elementary school Gugus Anai Silaing Bawah as many as 97 students. The sample of this research of 78 students. From the data analysis, Pearson Correlation value was 0,912 and r table with DF = 76 at 5% significance level 0f 0,22  which means that r count is greater that r table (0,912>0,22). And obtained a significance value of 0,000 is less that 0,05 (0,000<0,05). Thus it can be concluded there is a positive and significant relationship between learning motivation and student learning outcomes in learning social studies in class IV elementary school Gugus Anai Silaing Bawah. Keywords: Learning Motivation, Learning Outcomes, Social Studies